Joining of thermoplastic structures by Friction Riveting: A mechanical and a microstructural investigation on pure and glass reinforced polyamide sheets. (15th November 2018) - Gagliardi, F.; Conte, R.; Ciancio, C.; Simeoli, G.; Pagliarulo, V.; Ambrogio, G.; Russo, P.
Abstract: Friction Riveting is a spot joining, which consists in rotating a cylindrical rivet and inserting it into clamped sheets. In the first friction phase, the rotational speed and the applied axial force heat the material by friction plasticizing it. After that, the spindle rotation is stopped and the axial force is increased passing to the so called forging phase. Several working parameters, such as the rotational speed, the friction and forging times, and the friction and forging pressure, have to be optimized to achieve sound connections. In the proposed work, the attention was given to the joints of sheets made of a thermoplastic material with and without short glass fiber reinforcements. Rivets were made of Titanium Grade 2. The quality of the obtained results was verified by tensile tests. Moreover, microscopic observations were performed analyzing the material deformation and integrity inside the connection volume. The influences of the monitored process parameters on the above highlighted outputs were reported providing a guideline for the process execution.